Organ Transplantation as a Form of Realization of the Right to Life: A Constitutional and Legal Aspect - PIRBUDAGOVA, Diana Shamilyevna; VELIYEVA, Sabina Mukhtarovna (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
Kazakhstan and the Islamic Republic of Iran are two states that have common sea borders through the Caspian Sea, two friendly neighbors, successfully developing both bilateral cooperation and cooperation at the regional and international level. The relevance of this study is that today it is advisable to study the foreign policy of not only world powers, but also ‘non-knowing’ countries in order to determine the scenario for the development of relations between the two countries. The purpose of the article is to analyze and evaluate the geostrategic features of the interaction of Kazakhstan and Iran in the regional and global aspects. The leading approach to the study of this problem is the analysis method, which allowed to study the history of relations between Kazakhstan and Iran at different stages. This article attempts to determine the geostrategic features of the interaction between Kazakhstan and Iran in the regional and world aspect analyze and evaluate their bilateral relations.